Glycosylation sterically inhibits platelet adhesion to von Willebrand factor without altering intrinsic conformational dynamics. (3rd September 2019) - Tischer, Alexander; Machha, Venkata R.; Moon‐Tasson, Laurie; Benson, Linda M.; Auton, Matthew
Abstract: Background : A molecular basis for von Willebrand factor (VWF) self‐inhibition has been proposed by which the N‐terminal and C‐terminal flanking sequences of the globular A1 domain disulfide loop bind to and suppress the conformational dynamics of A1. These flanking sequences are rich in O‐linked glycosylation (OLG), which is known to suppress platelet adhesion to VWF, presumably by steric hindrance. The inhibitory mechanism remains unresolved as to whether inhibition is due to steric exclusion by OLGs or a direct self‐association interaction that stabilizes the domain. Objectives : The platelet adhesive function, thermodynamic stability, and conformational dynamics of the wild‐type and type 2M G1324S A1 domain lacking glycosylation ( Escherichia coli ) are compared with the wild‐type glycosylated A1 domain (HEK293 cell culture) to decipher the self‐inhibitory mechanism. Methods : Surface plasmon resonance and analytical rheology are utilized to assess Glycoprotein Ibα (GPIbα) binding at equilibrium and platelet adhesion under shear flow. The conformational stability is assessed through a combination of protein unfolding thermodynamics and hydrogen‐deuterium exchange mass spectrometry (HXMS). Results : A1 glycosylation inhibits both GPIbα binding and platelet adhesion. Glycosylation increases the hydrodynamic size of A1 and stabilizes the thermal unfolding of A1 without changing its equilibrium stability. Glycosylation does not alter the intrinsic conformational dynamics of the A1 domain. Conclusions : These studies invalidate the proposed inhibition through conformational suppression since glycosylation within these flanking sequences does not alter the native state stability or the conformational dynamics of A1. Rather, they confirm a mechanism by which glycosylation sterically hinders platelet adhesion to the A1 domain at equilibrium and under rheological shear stress.